Tinjauan Pengajuan Cuti Karyawan Menggunakan Aplikasi Human Resources Information System (HRIS) Di PT Pindad - Widia Nurdianti; Chandra Hendriyani (Jurnal Sekretaris dan Administrasi Bisnis, 2021)
This practical work report entitled "Review of Employee Leave Application Using Human Resource Information System (HRIS) at PT Pindad", with the background that PT Pindad is an industrial and manufacturing company engaged in the manufacture of rapidly developing military and commercial products in Indonesia requires efficient management systems in various fields. The focus of this research is how to implement employee leave applications using the HRIS application at PT Pindad Bandung. The purpose of this study was to determine how the implementation of employee leave applications at PT Pindad. In addition, to find out how to implement the theory of the implementation of leave such as filing to the filing of leave letters in the company. This research is a field research (field research) conducted at PT Pindad for 300 hours. Primary data were obtained from direct observations at PT Pindad, while secondary data were obtained from books, documents and articles relating to the research discussion. The results of this study indicate that there is already a match between theory and practice in filing leave and filing leave letters at PT Pindad. The implementation of leave has paid attention to the principles of effective and efficient by maximizing technology in the form of HRIS application. This was done to streamline time and to make recording easier. The system in the HRIS application also provides employee data reports on leave systematically by date. Making it easier to obtain employee data on leave. In order to avoid accumulation of employee leave requests.